Bleeding complications in pediatric ABO-incompatible kidney transplantation - Schäfer, Betti; Tönshoff, Burkhard; Schmidt, Jan; Golriz, Mohammad; Mehrabi, Arianeb; Gombos, Petra; Morath, Christian; Wühl, Elke; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2013)
ABO-incompatible renal transplantation (ABOi-RTx) following preconditioning with immunoadsorption (IA) and rituximab is a promising approach to facilitate living-related RTx. However, clinical experience is limited in pediatric patients.
Published online: 9 September 2012
Gesehen am 01.02.2022